2002
DOI: 10.1046/j.1365-2842.2003.00997.x
|View full text |Cite
|
Sign up to set email alerts
|

Surface texture and some properties of acrylic resins submitted to chemical polishing

Abstract: The effects of chemical polishing on dental acrylic resin properties are not well clarified. This study evaluated the effect of chemical and mechanical polishing on the residual monomer release (RM), Knoop hardness (KH), transverse strength (TS) and surface texture (ST) of a heat- and self-cured acrylic resin. Four groups were formed: GI-self-cured resin/mechanical polishing; GII-self-cured resin/chemical polishing; GIII-heat-cured resin/mechanical polishing; GIV-heat-cured resin/chemical polishing. Following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
72
1
17

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 14 publications
3
72
1
17
Order By: Relevance
“…The water absorption can affect the resistance of the polymer, acting as a plasticiser, which decreases the mechanical properties of the material 14,15,35 by reducing the forces between the polymer chains. Therefore, water molecules penetrate into the polymethylmethacrylate and promote separation of the polymer chains and a slight Some authors showed the effect of monomer release and additional polymerisation on the mechanical properties of acrylic resins after long period of water storage 37,38 . The polymethylmethacrylate tends to absorb water in its inhibition process, so that their crystal structures process a high internal energy 36 .…”
Section: Discussionmentioning
confidence: 99%
“…The water absorption can affect the resistance of the polymer, acting as a plasticiser, which decreases the mechanical properties of the material 14,15,35 by reducing the forces between the polymer chains. Therefore, water molecules penetrate into the polymethylmethacrylate and promote separation of the polymer chains and a slight Some authors showed the effect of monomer release and additional polymerisation on the mechanical properties of acrylic resins after long period of water storage 37,38 . The polymethylmethacrylate tends to absorb water in its inhibition process, so that their crystal structures process a high internal energy 36 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, chemical solutions may also have undesirable effects such as changes in color of dentures, increased roughness, and reduction in hardness of the denture acrylic resin surface (20,21). Furthermore, immersion of dentures in chemical solutions may lead to absorption of these liquids by the acrylic resin, which can then be released into the oral cavity (22) and leave an unpleasant residual taste (23).…”
Section: Introductionmentioning
confidence: 99%
“…However, the present concern about these materials is that there is insufficient scientific evidence regarding the properties of the high-impact acrylics and polyamide resins due to the small number of studies comparing the PMMA-based resins 18,19) .…”
Section: Introductionmentioning
confidence: 99%